2015
DOI: 10.1108/lodj-01-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

A “Tower of Babel”? – interrelations and structure of leadership constructs

Abstract: Purpose – The purpose of this paper is to provide a comprehensive examination of different leadership constructs investigated extensively, namely transformational and transactional leadership, laissez-faire, consideration, and initiating structure, as well as leader-member-exchange. The theoretical overlap as well as the empirical correlations between these constructs is explored. Design/methodology/approach – Overall, 735 correlations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 137 publications
1
21
0
1
Order By: Relevance
“…For instance, Derue et al (2011) showed that transformational leadership "has a significant relational component to it and overlaps conceptually and empirically with both initiating structure and consideration" (p. 38). Another meta-analytic study that also included transactional leadership, laissez-faire as well as LMX came to the same conclusion: there is considerable overlap between these leadership constructs (Rowold et al, 2015). A recent meta-analysis investigated more leadership styles and found that ethical, authentic, and servant leadership all correlate highly with transformational leadership (Hoch et al, 2018).…”
Section: Overlap Between Positive Leadership Stylesmentioning
confidence: 85%
See 2 more Smart Citations
“…For instance, Derue et al (2011) showed that transformational leadership "has a significant relational component to it and overlaps conceptually and empirically with both initiating structure and consideration" (p. 38). Another meta-analytic study that also included transactional leadership, laissez-faire as well as LMX came to the same conclusion: there is considerable overlap between these leadership constructs (Rowold et al, 2015). A recent meta-analysis investigated more leadership styles and found that ethical, authentic, and servant leadership all correlate highly with transformational leadership (Hoch et al, 2018).…”
Section: Overlap Between Positive Leadership Stylesmentioning
confidence: 85%
“…Despite several attempts to develop theoretical models on leadership and employee outcomes in leadership literature (see "Theoretical models on leadership and employee outcomes" below), no integrated process model of multiple positive leadership styles (and the translation of these styles into specific leader behavior) with regard to their shared effect on employee work engagement, based on theory, exists. Yet, meta-analyses with several positive leadership styles and leader behaviors indicate that there may be some construct redundancy (Banks et al, 2016(Banks et al, , 2018Derue et al, 2011;Hoch et al, 2018;Rowold et al, 2015). In addition, several positive leadership styles have relatively large correlations with work engagement (Banks et al, 2016;Hoch et al, 2018), which indicates the possibility of shared or common ground with regard to their effect on employee work engagement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, we firmly believe that, so far, we have yet to reach that point for any of the leadership constructs that are addressed in this paper. We need even more meta-analytic work in the nature of Hoch et al (2018) and Rowold et al (2015) that exceeds single-sample insights to eventually reach a consensus regarding the redundancy of a specific leadership model.…”
Section: Practical Implications For Setting Up Future Researchmentioning
confidence: 99%
“…More than that, the growth of social demand for an effective management system [29] and power institutions for political innovation sounds more and more actively. Various scholars talk about an objective request to study the youth motivation for participation in public and political projects in leadership positions [30], as well as the principles of organizing the work of leaders with members of their movements and organizations [31], [32], [33], [34]. Independent objects of analysis are the leadership phenomena for the young people studying in high school [35], as well as differences in leadership models of various representatives from certain gender groups [36].…”
Section: Discussionmentioning
confidence: 99%